The nature and structure of maternal parenting practices and infant behaviors in U.S. national and international samples - Bornstein, Marc H.; Putnick, Diane L.; Esposito, Gianluca; Pearson, Rebecca M. (Frontiers in Child and Adolescent Psychiatry, 2023)
Twenty maternal parenting practices and 15 behaviors of their 5½-month-old infants in a U.S. national sample (N = 360) and 9 international samples (N = 653) were microcoded from videorecords of naturalistic interactions at home and aggregated into domains. Altogether, the samples were recruited from Argentina, Belgium, Brazil, France, Israel, Italy, Japan, Kenya, as well as the United States. A previous test of three competing models of the nature and structure of the maternal parenting practices supported a hybrid 2 factor/6 domain model as superior to a 1-factor dimensional model and a multi-factor style model: Maternal parenting practices are structured into nurture, physical, social, didactic, material, and language domains undergirded by dyadic and extradyadic factors. Infant behaviors were organized into physical, social, exploration, nondistress vocalization, and distress communication domains. The current study sought to examine the links between these previously identified maternal domains and factors with infant activity domains using structural equation models. Results showed that mothers’ dyadic factor is associated with infant social behaviors with mother; and mothers’ extradyadic factor and encouragement of infant physical development are associated with infant exploration of the immediate physical environment and physical development. Infant distress communication (and less nondistress vocalization) is associated with more maternal nurturing. Mothers’ parenting practices in the middle of the first year of infant life are commonly structured and adapted to specific needs and developmental tasks of infants. Evaluation of mother-infant interactions with national and international samples permits a wide yet judicious analysis of common versus specific models of mother-infant relationships.